DETERMINING INFLUENCING FACTORS DEVELOPMENT OF THIRD-PARTY FUNDS: CASE STUDIES ON SHARIA BANKING IN INDONESIA - Baghas Budi Wicaksono; Yanti Pusparini; Rini Kurnia Sari (Az-Zahra Media Society, 2025)
Islamic banking in Indonesia has experienced rapid development over the past decade, as reflected in the increasing collection of third party funds (TPF), increasing contribution to gross domestic product in the financial services sector, and absorption of labor in the sector. This development is thought to be influenced by various macroeconomic indicators, such as benchmark interest rates, minimum cash reserves, government bond transactions, and other variables that play a role in the national monetary system. This study aims to analyze the influence of monetary indicators and labor on the development of third party funds in Islamic banking in Indonesia. The approach used is quantitative by utilizing secondary data analyzed using a multiple linear regression model. The results of the study indicate that labor in the Islamic banking sector and Bank Indonesia's benchmark interest rate have a significant effect on the development of third party funds. Labor has a positive effect, indicating that an increase in the number of workers encourages an increase in TPF collection. Conversely, the benchmark interest rate has a negative effect, indicating that a decrease in interest rates encourages an increase in third party funds in Islamic banking, in line with the public's preference for Islamic financial products when conventional interest rates decline.